TEACHER EDUCATION IN INDONESIA (An Account on the Development and Programs to Improve the Professional Qualification and the Competence of Indonesia Teaching Personnel) - Fahriany Fahriany (TARBIYA: Journal of Education in Muslim Society, 2014)
Abstract: Education is defined as a planned effort to establish a study environment and education process so that the student may actively develop his / her own potential to gain the religious and spiritual level, consciousness, personality, intelligence, behavior and creativity to him / herself other citizens and for the nations. The ultimate goal of   every  teaching and learning process is the success of the students to acquire the knowledge of subject matter being taught and one of the key successes in gaining the teaching learning objective is the teacher role. In fact, there are several aspects in order that the teacher professionalism may take place. To put the teacher professionalism into reality, it is not just from the teacher individually, but the surrounding, communities and the system where the teachers works and belong to, will give influence to it. The development of teacher education in Indonesia cannot be separated from the development of education in Indonesia. Since the independence in 1945, Indonesia has committed to make education available to all Indonesians citizens. This is due to the constitutional commitment stated that all citizens have the rights to get an education and the government has the responsibility to implement a national education system. DOI: 10.15408/tjems.v1i1.1107